Occupational exposure to chemicals, and health outcomes, among nail technicians in Johannesburg, South Africa - Keretetse, Goitsemang (University of the Witwatersrand, Johannesburg, 2023)
Introduction: Nail technicians are exposed to chemicals emitted from activities performed in nail salons, including simple buffing of nails, basic manicures and pedicures, application of nail polish, and the application and sculpting of artificial nails. The various products used during these processes may contain volatile organic compounds (VOCs), which pose a health risk to both the nail technicians and their clients. Associated health effects include skin, eye, and respiratory irritation, neurologic effects, reproductive effects, and cancer. The aim of this study was to effects within the formal and informal sectors in Johannesburg, South Africa. In this study, informal nail technicians are defined as those working in nail salons that are not licensed or registered with any formal enterprise or establishment, or in their own capacity. The objectives were 1) to estimate the prevalence of self-reported symptoms associated with the use of nail products, 2) to measure exposures to chemicals in nail products used in the formal and informal nail salons, 3) to investigate the feasibility and reliability of self-assessment of exposure as a method of estimating exposure to chemicals, and 4) to investigate the association between respiratory symptoms (chronic and acute) and chemical exposures in both formal and informal nail technicians. Methods: This was a cross-sectional study. A questionnaire, adapted from other studies, was piloted before being administered to the participating nail technicians. Data were collected from 54 formal and 60 informal nail technicians, regarding sociodemographic characteristics, perceptions of working with nail products, and self-reported symptoms of associated health effects. A subset of 20 formal and 20 informal nail technicians was conveniently selected from the 114 participants for the exposure assessment phase. The two groups were further divided into two groups of 10 for the controlled/expert exposure assessment (CAE) and the self-assessment of exposure (SAE). Personal 8-hr exposure measurements were performed using VOC and formaldehyde passive samplers attached to the participant’s breathing zone over three consecutive days. For the SAE approach, participants conducted their own exposure measurements, while the CAE approach was fully conducted by the principal researcher. Task-based measurements were carried out using a photoionization detector (PID) to measure peak concentrations during specific nail application activities. A probabilistic risk assessment was conducted to estimate the carcinogenic and non-carcinogenic life time risks from exposure to VOCs. Chemical analysis was conducted by a SANAS-accredited laboratory. After correcting for their respective evaporation rates, relative to the evaporation rate of d-limonene (the VOC with the lowest evaporation rate), the adjusted total VOC (TVOC) concentrations were calculated using the 13 VOCs that were detected at a frequency of 30% or more. VOC concentration data below the limit of detection (LoD) were imputed, using the regression on order statistic (Robust ROS) approach. The self-reported symptoms were categorised into neurological effects, respiratory effects, eye irritation, and skin irritation. The ACGIH additive effects formula was used to calculate the combined respiratory effect of selected VOCs. Different statistical tools were used to analyse the data for each objective. Results: Formal and informal nail technicians used different nail products, performed different nail applications, serviced different mean numbers of clients, and were exposed to different concentrations of selected VOCs. Acetone concentrations were higher in formal nail salons, due to the soak-off method used for removing existing nail applications, while methyl methacrylate (MMA) concentrations were higher in informal nail salons - related to acrylic methods being used more frequently in the informal than the formal nail salons. All VOC concentrations were below their respective occupational exposure limits, with the exception of formaldehyde (0.21 mg/m3). TVOC levels were higher in formal nail salons, due to the bystander effect from multiple nail technicians performing nail applications simultaneously. Sixty percent of the informal nail technicians reported health-related symptoms, compared to 52% of the formal nail technicians, and informal male nail technicians reported more symptoms than their female counterparts. All nail technicians' median and 95th percentile non-cancer risks exceeded the acceptable risk of 1 for xylene, 2-propanol, and benzene, while the cancer risk estimates (medians and 95th percentiles) for benzene and formaldehyde exceeded the US EPA cancer risk threshold of 1 x 10-6. Conclusion: This is the first study to assess exposures to VOCs in the often-overlooked informal sector and compare these exposures with those in the formal sector of the nail industry. Personal breathing zone concentration data for nail salon workers were generated in this study, including the informal sector, which is always challenging to access for research. Although banned in many countries, MMA is still used in South Africa in the informal nail sector. The SAE study showed that participatory research is feasible and enables a more reliable estimate of the exposure by expanding the amount of data. Using a combination of shift and task-based measurements was particularly effective in creating exposure profiles of employees and identifying activities that require targeted interventions. There is a need for the nail industry, especially the informal salons, to be more closely regulated, concerning the hazardous chemicals frequently encountered in nail products. Nail salons should reduce exposure frequency by regulating working hours, making informed decisions regarding the procurement of nail products, and adopting safe work practices to reduce emissions from harmful chemicals and thus exposure among nail salon workers and their clients.
Original published work submitted in fulfilment of the requirements for the degree of Doctor of Philosophy (Public Health), to the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Volatile organic compounds; Passive sampling; Task-based monitoring; VOC profile; Formal sector; Informal sector; Bystander exposure; Health effects; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education